ABI4 Regulates Primary Seed Dormancy by Regulating the Biogenesis of Abscisic Acid and Gibberellins in Arabidopsis - Shu, Kai; Zhang, Huawei; Wang, Shengfu; Chen, Mingluan; Wu, Yaorong; Tang, Sanyuan; Liu, Chunyan; Feng, Yuqi; Cao, Xiaofeng; Xie, Qi (PLoS genetics, 2013)
Seed dormancy is an important economic trait for agricultural production. Abscisic acid (ABA) and Gibberellins (GA) are the primary factors that regulate the transition from dormancy to germination, and they regulate this process antagonistically. The detailed regulatory mechanism involving crosstalk between ABA and GA, which underlies seed dormancy, requires further elucidation. Here, we report that ABI4 positively regulates primary seed dormancy, while negatively regulating cotyledon greening, by mediating the biogenesis of ABA and GA. Seeds of the Arabidopsis abi4 mutant that were subjected to short-term storage (one or two weeks) germinated significantly more quickly than Wild-Type (WT), and abi4 cotyledons greened markedly more quickly than WT, while the rates of germination and greening were comparable when the seeds were subjected to longer-term storage (six months). The ABA content of dry abi4 seeds was remarkably lower than that of WT, but the amounts were comparable after stratification. Consistently, the GA level of abi4 seeds was increased compared to WT. Further analysis showed that abi4 was resistant to treatment with paclobutrazol (PAC), a GA biosynthesis inhibitor, during germination, while OE-ABI4 was sensitive to PAC, and exogenous GA rescued the delayed germination phenotype of OE-ABI4. Analysis by qRT-PCR showed that the expression of genes involved in ABA and GA metabolism in dry and germinating seeds corresponded to hormonal measurements. Moreover, chromatin immunoprecipitation qPCR (ChIP-qPCR) and transient expression analysis showed that ABI4 repressed CYP707A1 and CYP707A2 expression by directly binding to those promoters, and the ABI4 binding elements are essential for this repression. Accordingly, further genetic analysis showed that abi4 recovered the delayed germination phenotype of cyp707a1 and cyp707a2 and further, rescued the non-germinating phenotype of ga1-t. Taken together, this study suggests that ABI4 is a key factor that regulates primary seed dormancy by mediating the balance between ABA and GA biogenesis.